A method to acquire cross‐domain requirements based on Syntax Direct Technique. (28th June 2021) - Liu, Huaxiao; Zhang, Mengxi; Liu, Lei; Liu, Zhou
Abstract: With the rapid increase in the number of Apps, the requirement of users has also become extremely complex. Developers have to continuously acquire innovative requirements that provide the guideline for developing more competitive products. However, traditional methods to acquire requirements are not suitable for the App development due to the disadvantage that it cannot interact with users directly. Besides, some methods that use text and data analysis to acquire requirements automatically are hard to expand innovative products because they are often confined to the specific App or the same domain. Therefore, to attract more new users, developers try to find new portable inspiration from other domains for enriching the functions of the App. In this article, we propose a feature extraction method from the descriptions of Apps and use similarity matching to acquire cross‐domain requirements. Our experiments have verified that the Precision, the Recall, and the F‐measure are all as high as 80% of our feature extraction method. Besides, the requirements list we recommend also makes a good performance in terms of reusability with the average Reuse Rank of 59.33% and average Adjusted Functional Points of 7.49, the adaptability gets an average score of 3.3, and the average score of operability is 3.